ANALISIS KETERAMPILAN BERPIKIR KRITIS PADA INDIKATOR MEMBERIKAN PENJELASAN LEBIH LANJUT MATERI HIDROKARBON - Herunata Herunata; Reza Rewindi Amayliadevi; Hayuni Retno Widarti (J-PEK (Jurnal Pembelajaran Kimia), 2020)
The purpose of this research measured the ability of critical thinking skills on hydrocarbon topic with focused on the further-explanation-indicators in 11th MIA grade students 2018/2019 academic year. This research used a descriptive quantitative research design. The data was analyzed came from 133 students test results in answering questions of critical thinking skills instrument what developed by Rodliyah (2018). The aspect of critical thinking skills with the further-explanation-indicators consisting of five reasoned multiple choice questions. Analyzing were done from students’s answering whose 1 scored, then categorized by percentage according to Karim (2015). The results showed that students had critical thinking skills with the further-explanation-indicators on hydrocarbon topic including a) 57,90% on the subject of isomeric hydrocarbon compounds (low category), b) 67,67% on the subject of the use of hydrocarbon compounds (average category), c) 89,47% on the subject of the physical and chemical properties of hydrocarbon compounds : the physical properties of hydrocarbon compounds (very high category), d) 55,64% on the subject of the physical and chemical properties of hydrocarbon compounds : combustion reaction of hydrocarbon compounds (low category), and e) 11,28% on the subject of nomenclature of hydrocarbon compounds (very low category).